2022
DOI: 10.1097/gme.0000000000002079
|View full text |Cite
|
Sign up to set email alerts
|

Resistance training for postmenopausal women: systematic review and meta-analysis

Abstract: Importance: Numerous studies have been published assessing the effects of resistance muscle training to mitigate menopausal symptoms, given the endocrine muscle function and its metabolic regulation. Therefore, mapping and synthesizing high-quality studies are necessary to help clinical decisions.Objective: The aim of this study was to assess the effects (benefits and harms) of resistance muscle training for postmenopausal women.Evidence Review: Electronic searches were conducted in MEDLINE (via PubMed), EMBAS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 43 publications
0
5
0
Order By: Relevance
“…• avoiding triggers (e.g., spicy foods, lights, comforters, and predictable emotional reactions); • cool down the environment (e.g., by turning down the thermostat, using fans, and cooling gel pads [gel-filled sheets that are placed on a mattress and dissipate body heat]); • Wearing layered clothing, which can be removed when needed can help; and • exercise and weight loss [86][87][88][89][90][91]. Devices that cool skin receptors may help some women; they can be worn as cuffs or necklaces or placed on the neck's back.…”
Section: Managementmentioning
confidence: 99%
“…• avoiding triggers (e.g., spicy foods, lights, comforters, and predictable emotional reactions); • cool down the environment (e.g., by turning down the thermostat, using fans, and cooling gel pads [gel-filled sheets that are placed on a mattress and dissipate body heat]); • Wearing layered clothing, which can be removed when needed can help; and • exercise and weight loss [86][87][88][89][90][91]. Devices that cool skin receptors may help some women; they can be worn as cuffs or necklaces or placed on the neck's back.…”
Section: Managementmentioning
confidence: 99%
“…One high-quality review 49 reported a bene t of resistance training on incidence of moderate or severe hot ash episodes. This is based on a single, very small RCT (58 participants) and the effect estimate re ects high levels of imprecision.…”
Section: Vasomotor Symptomsmentioning
confidence: 99%
“…One high-quality review 49 included one RCT (36 participants) comparing aerobic versus resistance training for 8 weeks. No differences were observed in total menopause quality-of-life domains.…”
Section: Aerobic Exercise Versus Resistance Trainingmentioning
confidence: 99%
See 1 more Smart Citation
“…It is unclear whether air pollution can also contribute to a more problematic menopause transition in the form of increased menopausal symptoms. Although studies on possible protective role of PA with respect to the symptoms of menopause exist, 53‐56 more research is needed to better understand whether these benefits are realized to the same extent within environments with varying levels of ambient air pollution, while accounting for the effects of important covariates such as fitness level, body composition status, or neuroticism, all which have been also associated with menopausal symptoms 42,57,58 . In this study, we used data from the Healthy Aging in Industrial Environment Program 4 (4HAIE) study to examine the associations between daily PA (Fitbit steps) and menopausal symptoms in a subsample of middle-aged women recruited from the 4HAIE cohort residing in areas of high versus low relative ambient air pollution.…”
mentioning
confidence: 99%